Use of Er:YAG laser in the treatment of vulvar lichen sclerosus - Matilde Gómez-Frieiro, MD; Elena Laynez-Herrero, MD (Wolters Kluwer, 2019)
Objective: The aim of this research was to evaluate the efficacy and safety of Er:YAG lasers to improve signs and symptoms of vulvar lichen sclerosus. Methods: The study population consisted of 28 women with symptomatic vulvar lichen sclerosus. Three nonablative, thermal-only Er:YAG laser treatment sessions (7 J/cm2, 2 Hz, 7 mm spot) were performed at 4-week intervals. Each patient was asked about the presence of symptoms, such as itching, pain, and coital pain. Clinical diagnosis was established on the basis of the presence of lesions such as hypopigmentation, ecchymosis, hyperkeratosis, excoriations, or fissures. The affected areas were divided by zones (clitoris, introitus, labia minora, labia majora, perineum, labial fusion, and effacement) and were visually evaluated. Based on the presence of symptoms, lesions, and affected zones, a scale with a maximum of 14 scores was established for use before and after treatment. The impact of lichen sclerosus on patients' lives before and after treatment was evaluated with an 11-point visual analogue scale, and treatment discomfort was assessed at each session. Results: After analysis of each scoring component, individual statistically significant reductions were observed in itching, pain, ecchymosis, excoriations, and hypopigmentation. Conclusion: The Er:YAG laser is a safe, well tolerated, and effective method for the adjuvant treatment of vulvar lichen sclerosus. Three sessions with monthly intervals using the indicated parameters can quantifiably reduce the impact of lichen sclerosus on patients' lives. Keywords: erbium laser, vulvar lichen sclerosus